Affecting behavioural change through empowerment: conceptual insights from theory and agricultural case studies in South Asia - Serena H. Hamilton; Wendy S. Merritt; Lucy Carter; Arnab Chakraborty; Michaela Cosijn; Lilly Lim-Camacho; Rajeshwar Mishra; Geoff Syme; Mahanambrota Das; Dhananjay Ray (Regional Environmental Change, 2022)
Affecting behavioural change is a common underlying goal across environmental and agricultural sciences, from climate change mitigation and adaptation, biodiversity conservation, water management, to crop diversification. However, many projects fail to drive or sustain change despite sound science and good intentions. This paper draws on existing theories of behavioural change to construct a conceptual framework that explores pathways to initiate and sustain change through the lens of empowerment, self-efficacy and agency. The framework is demonstrated with case studies from a project in India and Bangladesh that examined social inclusion of marginalised and poor farmers in the context of intensifying agriculture. The framework and case studies highlight that a number of conditions are needed to affect meaningful change including that target beneficiaries are suitably motivated, believe in their own capability and power to enact change and have access to the necessary resources. We propose the framework as a tool to help project teams explore the underlying elements of the process of change when designing, implementing and assessing agricultural or environmental projects and interventions. We contend that behavioural and social change needs to be explicitly fostered in such endeavours to achieve better and longer-term outcomes for the people and environment.

A comprehensive insight on ocular pharmacokinetics - Vibhuti Agrahari; Abhirup Mandal; Vivek Agrahari; Hoang M. Trinh; Mary Joseph; Animikh Ray; Hicheme Hadji; Ranjana Mitra; Dhananjay Pal; Ashim K. Mitra (Drug Delivery and Translational Research, 2016)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)